ANALISA WAKTU TEMPUH KENDARAAN RODA DUA PADA RUAS JALAN ARTERI PRIMER KOTA SAMARINDA - Rahmawati, Rini (KURVA S JURNAL MAHASISWA, 2014)
Travel time (Travel Time) is the average time used the vehicle to travel the road segment with certain length, including delay, downtime, the average travel time of vehicles derived from comparing the length of the road segment. The purpose of this study was to analyze the travel time of light vehicles on arterial road network in the city of Samarinda.Primary data is needed is the vehicle speed data per second through direct surveys by using the tools of GPS (global positioning system). SecondaryÂ is supporting data covering the width and number of roads in the road network were surveyed. From the research and analysis of data obtained by the path of travel, speed fluctuation per second, and the parameters of vehicle movement patterns. Modeling light vehicle travel time were analyzed using multiple linear regression (SPSS 20.0). There are two variables that significantly affect the travel time of the vehicle. Both of these variables showed signs of rationality test the suitability of the travel time.Where is increasing its variable value is positive lead vehicle travel time will be growing, while the increasing value of the variable is negative causing the vehicle travel time will be reduced